Anticonvulsant Effects of Aerial Parts of Extract in Mice: Involvement of Benzodiazepine and Opioid Receptors - Amir Rashidian PharmD, PhD; Fatemeh Kazemi PharmD; Saeed Mehrzadi PhD; Ahmad Reza Dehpour PharmD, PhD; Shahram Ejtemai Mehr PharmD, PhD; Seyed Mahdi Rezayat PharmD, PhD (SAGE Publishing, 2017)
To evaluate the anticonvulsant activity of the aerial parts of Verbena officinalis used traditionally by local Iranians for the treatment of convulsion. The anticonvulsant activity of the extract was assessed in pentylenetetrazole (PTZ) and maximal electroshock (MES) induced seizures in mice. Diazepam was used as reference drug. In addition, for investigating the mechanism of V officinalis in PTZ model, flumazenil and naloxone were injected before V officinalis . The extract showed no toxicity and significantly increased the period taken before the onset and decreased the duration of the seizures induced by PTZ. In the MES test, V officinalis displayed significant reduction in hind limb tonic extension duration in a dose-dependent manner. The results propose that V officinalis ethanolic extract has anticonvulsant activity against seizure. It seems that these effects may be related to potentiating of GABAergic system. Moreover, this study supports the use of this plant by local Iranians in order to treat convulsion.